The Military Qassam , Its duties and role,documents the records of Homs and the legitimate Hama in the thirteenth centuryAH.Nineteenth centurystudy documentary (Journal of Hama University, 2020)
The research deals with the tasks of the qisma judges, their role and powers in the state of Damascus, the manner in which they are appointed, the duration of their services and places of residence and the issues assigned to them, such as. the Hajj and contract of the Qur’an and divorce, how to distribute inheritances, identifying guardians to the orphans' legacies and their inheritance, counting the  inheritance in the smallest detail, the issue of selling, exchanging and liberating slavery, and implementing ,to rule according to Islamic law, and their position on the manipulation of the Qassams or others in the inherited property, knowing that their role and tasks are identical to the tasks of the military Qassam, But the Ottoman state and to preserve the heirs of the deceased from its soldiers, formed a monitoring committee for the Qassam to avoid  the heirs of financial blackmail or similar Mattirs.